Overcome Chemoresistance: Biophysical and Structural Analysis of Synthetic FHIT-Derived Peptides - Scala, Maria Carmina; Di Micco, Simone; Lanzillotta, Delia; Musella, Simona; Di Sarno, Veronica; Parrino, Barbara; Cascioferro, Stella Maria; Bifulco, Giuseppe; Trapasso, Francesco; Campiglia, Pietro; Sala, Marina (Frontiers in Molecular Biosciences, 2021)
The fragile histidine triad (FHIT) protein is a member of the large and ubiquitous histidine triad (HIT) family of proteins. On the basis of genetic evidence, it has been postulated that the FHIT protein may function as tumor suppressor, implying a role for the FHIT protein in carcinogenesis. Recently Gaudio et al. reported that FHIT binds and delocalizes annexin A4 (ANXA4) from plasma membrane to cytosol in paclitaxel-resistant lung cancer cells, thus restoring their chemosensitivity to the drug. They also identified the smallest protein sequence of the FHIT still interacting with ANXA4, ranging from position 7 to 13: QHLIKPS. This short sequence of FHIT protein was not only able to bind ANXA4 but also to hold its target in the cytosol during paclitaxel treatment, thus avoiding ANXA4 translocation to the inner side of cell membrane. Starting from these results, to obtain much information about structure requirements involved in the interaction of the peptide mentioned above, we synthetized a panel of seven peptides through an Ala-scan approach. In details, to study the binding of FHIT derived peptides with ANXA4, we applied a combination of different biophysical techniques such as differential scanning fluorimetry (DSF), surface plasmon resonance (SPR), microscale thermophoresis (MST). Circular Dichroism (CD) and nuclear magnetic resonance (NMR) were used to determine the conformational structure of the lead peptide (7-13) and peptides generated from ala-scan technique. The application of different biophysical and structural techniques, integrated by a preliminary biological evaluation, allowed us to build a solid structure activity relationship on the synthesized peptides.